Faithful Translation Applied in Translating Webtoon I Love Yoo - Fitriani, Nur; Jayantini, I Gusti Agung Sri Rwa; Utami, Ni Made Verayanti (Indonesian Journal of English Language Studies (IJELS), 2021)
The aim of translation is to transfer meaning from the source language to the target language. There are some methods that can be used in translating the text, one of them is faithful translation. Faithful translation method is a method that reproduces the exact contextual meaning of the original within the limits of the grammatical structures of the target language. This study focuses on analyzing faithful translation methods in the webtoon “I Love Yoo”. The objective of this study is to identify how the faithful translation method is applied in translating webtoon Ï Love Yoo”. The method applied in this study is qualitative descriptive method and the data were taken from the 1st to 10th episode of webtoon “I Love Yoo”. The data collected were analyzed by reading both versions of the webcomic, classified each sentence according to the translation methods and explained why the sentences are included into each translation method. To analyze the data, this study used the theory translation method proposed by Newmark (1988). It is found that 8 translation methods were applied but faithful translation method is most frequently used because the translator translates cultural terms and maintains the degree of grammatical and lexical faithfully to the intentions and the text-realisation of the source language writer.